(untitled) (Oratio Directa, 2018)
This literature study examines Social Penetration Theory as a framework for understanding self-disclosure and interpersonal closeness. The analysis focuses on the progression of relationships from superficial exchanges to deeper personal communication, the reciprocal character of disclosure, depenetration, and the role of rewards and costs. The theory explains four relational stages through the onion-layer analogy: orientation, exploratory affective exchange, affective exchange, and stable exchange. Although useful for explaining interpersonal development, the theory has limitations because culture, demographic characteristics, values, and non-instrumental motives also influence disclosure.